12 Novel clonal groups of Leptospira infecting humans in multiple contrasting epidemiological contexts in Sri Lanka. - Dinesha Jayasundara; Indika Senavirathna; Janith Warnasekara; Chandika Gamage; Sisira Siribaddana; Senanayake Abeysinghe Mudiyanselage Kularatne; Michael Matthias; Jean-François Mariet; Mathieu Picardeau; Suneth Agampodi; Joseph M Vinetz (Public Library of Science (PLoS), 2021)
Leptospirosis is a ubiquitous zoonotic disease and a major clinical challenge owing to the multitude of clinical presentations and manifestations that are possibly attributable to the diversity of Leptospira, the understanding of which is key to study the epidemiology of this emerging global disease threat. Sri Lanka is a hotspot for leptospirosis with high levels of endemicity as well as annual epidemics. We carried out a prospective study of Leptospira diversity in Sri Lanka, covering the full range of climatic zones, geography, and clinical severity. Samples were collected for leptospiral culture from 1,192 patients from 15 of 25 districts in Sri Lanka over two and half years. Twenty-five isolates belonging to four pathogenic Leptospira species were identified: L. interrogans, L. borgpetersenii, L. weilii, and L. kirschneri. At least six serogroups were identified among the isolates: Autumnalis (6), Pyrogenes (4), Icterohaemorrhagiae (2), Celledoni (1), Grippotyphosa (2) and Bataviae (1). Seven isolates did not agglutinate using available antisera panels, suggesting new serogroups. Isolates were sequenced using an Illumina platform. These data add 25 new core genome sequence types and were clustered in 15 clonal groups, including 12 new clonal groups. L. borgpetersenii was found only in the dry zone and L. weilii only in the wet zone. Acute kidney injury and cardiovascular involvement were seen only with L. interrogans infections. Thrombocytopenia and liver impairment were seen in both L. interrogans and L. borgpetersenii infections. The inadequate sensitivity of culture isolation to identify infecting Leptospira species underscores the need for culture-independent typing methods for Leptospira.